1999
DOI: 10.1002/(sici)1098-1136(19990215)25:4<343::aid-glia4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Strongly compromised inflammatory response to brain injury in interleukin-6-deficient mice

Abstract: Injury to the central nervous system (CNS) elicits an inflammatory response involving activation of microglia, brain macrophages, and astrocytes, processes likely mediated by the release of proinflammatory cytokines. In order to determine the role of interleukin‐6 (IL‐6) during the inflammatory response in the brain following disruption of the blood–brain barrier (BBB), we examined the effects of a focal cryo injury to the fronto‐parietal cortex in interleukin‐6‐deficient (IL‐6−/−) and normal (IL‐6+/+) mice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 70 publications
6
92
0
4
Order By: Relevance
“…We also evaluated the expression level of IL-6, a pleiotropic cytokine that has been shown to be neuroprotective in several types of brain injury including stroke and TBI (Morganti-Kossmann et al, 2002;Suzuki et al, 2009;Ziebell and MorgantiKossmann, 2010). Interleukin-6 may actually attenuate oxidative damage, exert antiapoptotic actions, and participate in brain repair processes (Penkowa et al, 1999;Stahel et al, 2000). We found that LPS-preconditioned mice at 5 days interval had increased IL-6 mRNA expression after TBI compared with saline-treated mice, supporting the hypothesis that stimulation of production of neuroprotective factors (IFNb and IL-6) is part of the mechanisms by which LPS preconditioning confers neuroprotection.…”
Section: Discussionsupporting
confidence: 69%
“…We also evaluated the expression level of IL-6, a pleiotropic cytokine that has been shown to be neuroprotective in several types of brain injury including stroke and TBI (Morganti-Kossmann et al, 2002;Suzuki et al, 2009;Ziebell and MorgantiKossmann, 2010). Interleukin-6 may actually attenuate oxidative damage, exert antiapoptotic actions, and participate in brain repair processes (Penkowa et al, 1999;Stahel et al, 2000). We found that LPS-preconditioned mice at 5 days interval had increased IL-6 mRNA expression after TBI compared with saline-treated mice, supporting the hypothesis that stimulation of production of neuroprotective factors (IFNb and IL-6) is part of the mechanisms by which LPS preconditioning confers neuroprotection.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, IL-6 was also found to be neuroprotective in vivo upon cryolesion induced brain damage, as shown recently in IL-6 deficient mice (Penkowa et al 1999). However, similarly to other cytokines (MunozFernandez and Fresno 1998), Il-6 may exert both beneficial and detrimental activities in neuronal tissue depending on yet undefined factors (Campbell 1998;Gadient and Otten 1997;Merrill and Jonakait 1995).…”
mentioning
confidence: 55%
“…These studies, as well as those carried out in IL-6 KO mice (10,51), demonstrated that IL-6 is a major cytokine regarding the control of MT isoforms in the CNS. In the present report, we have examined whether the astrocyte-targeted expression of TNF-␣, which causes a chronic-progressive neurological disorder, is associated with altered expression of the MT isoforms.…”
Section: Introductionmentioning
confidence: 76%
“…Other sections were preincubated in 10% goat serum (In Vitro, DK, code 04009-1B) in TBS/Nonidet with 0.01% TBS/Nonidet for 30 min at room temperature, followed by incubation with blocking solutions A ϩ B from the HistoMouse-SP kit to quench endogenous mouse IgG (Zymed Lab. Inc., code 95-9544), followed by incubation overnight for double immunofluorescence stainings with the following primary antibodies: mouse anti-horse MT-I ϩ II (IgG) 1:50 (Dakopatts, DK, code M0639), and rabbit anti-MT-III (IgG) 1:1000 (9,11,51). These primary antibodies were detected using goat anti-mouse IgG conjugated with coumarin/ AMCA 1:50 (Dakopatts, DK, code W0477) and goat anti-rabbit IgG conjugated with Texas Red 1:50 (Jackson ImmunoResearch Lab.…”
Section: Immunofluorescence Histochemistrymentioning
confidence: 99%